DETERMINANTS OF NET PROFIT MARGIN IN AICO ENERGY TECHNOLOGY, PT IN BALIKPAPAN - Syahril Hasan; Anita De Grave (Universitas Muhammadiyah Kalimantan Timur, 2021)
This study aims to determine the low Net Profit Margin at Aico Energy Technology, PT in Balikpapan. The variable used is Net Profit Margin as the dependent variable, while the independent variables are Cash Turnover (X1), Accounts Receivable Turnover (X2), and Inventory Turnover (X3). Using a sample of financial statements for seven years, the data analysis method was carried out with multiple linear regression models, classical assumptions, and hypothesis testing. Based on the results of the f-test showed that Cash Turnover, Accounts Receivable Turnover and Inventory Turnover simultaneously had a significant effect on the Net Profit Margin of Aico Energy Technology PT in Balikpapan. T test, Accounts Receivable Turnover has a significant effect, Receivable Turnover Variable partially has a significant effect on Net Profit Margin at Aico Energy Technology, PT in Balikpapan.